Avaliação das condições térmicas em escolas públicas no semiárido paraibano segundo os princípios da arquitetura bioclimática - Pinheiro, Wilma Fernandes (2023)
Based on the bioclimatic approach to architecture, which involves an interrelationship between the built environment, climatic elements and human well-being, this study sought to analyze the principles of local bioclimatic architecture and its relationships with thermal comfort conditions in two public schools located in the region. semi-arid region of the Brazilian Northeast, specifically in the city of Cajazeiras/PB. For the bioclimatic assessment of the schools, monitoring and recording of climate variables (air temperature and relative humidity) were used in two stages, using HOBO Data Logger U-10 thermo-hygrometers installed in two classrooms of each school. , unoccupied, with open windows and closed doors. In the first stage, air temperature and relative humidity data were collected in 7 days of the region's dry period (from September 15 to 22, 2021). In the second stage, microclimatic data were collected during 7 days in months of the region's rainy season (January 31, 2022 to February 7, 2022) for comparative analysis purposes. The collection with unoccupied rooms allowed greater control of the data, as it was not influenced by the internal heat produced by the occupation and also by the interference of the cooling system. In addition to the classrooms, two external points, in each of the schools, served as a reference for the external temperature. The results showed that the four monitored internal points presented Thermal Discomfort Index (TDI) ranging from uncomfortable to partially comfortable. In addition, indoor environments, at night and in the early hours of the day, had higher temperatures than outdoor environments. These findings proved that the built environments evaluated in this research are disconnected with the appropriate bioclimatic principles for this semi-arid region of Paraíba. Comparison of climatological data allowed us to observe that classrooms with cross ventilation are more favorable for thermal comfort in the early hours of the day. The relations of the data collected with the materials used in the roof, found that the fiber cement tiles contribute to the increase in temperatures and the ceramic tiles and the inclined slab absorb less thermal radiation towards the interior of the environment. Proximity to vegetation in the immediate surroundings was another differentiating parameter, influencing the decrease in temperatures and, above all, the increase in relative humidity.